The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.neubiorev.2020.01.016
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive ability and education: How behavioural genetic research has advanced our knowledge and understanding of their association

Abstract: Cognitive ability and educational success predict positive outcomes across the lifespan, from higher earnings to better health and longevity. The shared positive outcomes associated with cognitive ability and education are emblematic of the strong interconnections between them. Part of the observed associations between cognitive ability and education, as well as their links with wealth, morbidity and mortality, are rooted in genetic variation.The current review evaluates the contribution of decades of behaviou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 184 publications
(226 reference statements)
1
36
0
Order By: Relevance
“…Quality early education increases educational success and adult productivity, allowing for society's development [6][7][8]. One of the aspects that defines quality early education is teachers being able to adapt their practices to the needs of children [21,22,82]. As reflected in the T-patterns detected in our study, children have distinct and ever-changing trajectories and needs that require specific instruction and support to enable optimal growth [22,29].…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…Quality early education increases educational success and adult productivity, allowing for society's development [6][7][8]. One of the aspects that defines quality early education is teachers being able to adapt their practices to the needs of children [21,22,82]. As reflected in the T-patterns detected in our study, children have distinct and ever-changing trajectories and needs that require specific instruction and support to enable optimal growth [22,29].…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, if education program do not respect their characteristics and differences, they may experience continuous failure and their keenness for learning can be "turned off". This results in the need for pedagogical work more sensitive to the individual differences [21]. Therefore, to be able to offer the education practice more suitable for each children taken into account their differences, including their different genetic propensity to learn, reason and solve problems, is a pending challenge.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies on PGS in educational settings have shown that currently, PGS can predict a composite academic achievement measure, educational attainment, and reading comprehension abilities with up to 10%, 15%, and 5% accuracy, respectively 13 , 25 27 . As molecular genetics methods get better and reference sample sizes get bigger, the predictive power of PGS to educationally relevant outcomes are expected to substantially increase, with some research estimating predictive limits as high as about 50% in student outcomes 13 , 28 . However, adding to the complexity of testing the incremental value of using PGS as part of personalized education, the current and hypothesized future predictive values of PGS are currently debated.…”
Section: Introductionmentioning
confidence: 99%